TOKOH LAISA SEBAGAI SIMBOL KETANGGUHAN PEREMPUAN DALAM NOVEL DIA ADALAH KAKAKKU KARYA TERE LIYE KAJIAN FEMINISME - Lilik Aulia; Elsa Mulya Karlina (JIP: Jurnal Ilmu Pendidikan, 2025)
This study is entitled "The Character of Laisa as a Symbol of Women's Resilience in the Novel Dia Adalah Kakakku by Tere Liye Feminism Study". This study aims to describe how the symbol of women's resilience is narrated through the character of Laisa. This study uses a qualitative method with a literature approach and is supported by Simone de Beauvoir's feminist theory. This refers to a research approach that produces descriptive data in the form of written data resulting from observations of an object, namely the Novel. Data is obtained through narratives, dialogues, quotes, and actions of characters that show strength, patience, independence, and an attitude of never giving up. The problem studied in this study is how the symbol of women's resilience is represented through the character of Laisa in the novel Dia Adalah Kakakku by Tere Liye. The results of the study show that Laisa reflects a tough woman figure both physically and psychologically. This resilience is symbolized through sacrifice, struggle, struggle, and the great responsibility she bears in her family.